Quality By Design Enabled Carvedilol Self-Nanoemulsifying Drug Delivery System: In-Vitro and In-Vivo Characterization for Improved Management of Hypertension - Swain, Surya Kanta; Maharana, Rajib Lochan; Mahapatra, Santosh Kumar; Ghose, Debashish; Jena, Bikash Ranjan (Biomedical Sciences and Clinical Medicine, 2025)
Objective Due to poor absorption and substantial hepatic first-pass metabolism, carvedilol, a commonly used cardiovascular drug for hypertension and congestive heart failure, has a low and variable bioavailability. In order to enhance carvedilol solubility and prevent the first-pass impact, the current research work intends to produce SNEDDS of the drug using systematic DoE. This will ultimately increase its bioavailability. METHODS By choosing the critical process parameters as factors that influenced the intended responses, quality by design was made possible. Oil and S/CoS were examined for pre-isotropic compatibility and formu-lation enhancement using Design of Experiment software. The cumulative percentage of drug release (QT30) in minutes, emulsification time (ET) in minutes, and emulsion globule size (nm) of the nano formulations were measured using a heating-cooling cycle and phase separation. To enhance carvedilol biopharmaceutical efficacy and oral bioavailability for the therapeutic management of cardiovascular disease. The carvedilol loaded self-nano emulsifying drug delivery system has been prepared by admixture method with selected oil, surfactant, and co-surfactant based on higher mean saturation solubility of drug. QbD approach presents an effective method to develop SNEDDS formulations of carvedilol with enhanced Using Design of experiments software, oil (Lauroglycol FCC), surfactant (Tween 20), and co-surfactant (Propylene glycol) were optimized for pre-isotropic compatibility and formulation development. RESULTS The prepared SNEDDS exhibited non-Fickian mechanism of drug release, according to in vitro drug release kinetic data. The optimised formulation had uniform shape and nanosize with no physical incompatibilities between the selected excipients and the pure drug based on SEM, DSC and FT-IR. After six months of storage, remains stable, according to accelerated stability tests. CONCLUSIONS In order to improve the therapeutic treatment of cardiovascular disease, the QbD approach presents an effective method to develop SNEDDS formulations of carvedilol with enhanced oral bioavailability and biopharmaceutical performance.